Aggressive natural killer-cell leukemia: Classical presentation of a rare disease - Priya M Jacob; Rekha A Nair; Anila Kunjulekshmi Amma Raveendran Nair (Wolters Kluwer Medknow Publications, 2014)
Aggressive natural killer-cell leukaemia is a rare aggressive form of natural killer-cell neoplasm. We report a case of a 40-year-old male who presented with jaundice, raised blood counts,generalised lymphadenopathy and hepatosplenomegaly. The diagnosis was established by flow cytometric analysis of bone marrow aspirate. The patient, however, succumbed to his illness within 2 weeks of starting chemotherapy. To the best of our knowledge, this is the third reported case from India.